How Does Media Literacy Affect Smoking and Vaping Behaviors among Adolescents? A Systematic Literature Review - Danang Wahansa Sugiarto; Fajrin Violita (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Smoking remains a global health problem. In addition to conventional cigarettes, a new type of cigarette has emerged called electronic cigarettes (e-cigarettes or vapes). It is known that media exposure greatly influences adolescents' initiation into smoking. Based on this, a concept and intervention called media literacy was developed. This study examines how media literacy is measured or implemented in adolescents' smoking behavior, both conventional and electronic. Methods: This study is a systematic literature review, and a review protocol based on the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) was used. A literature search using 4 reputable databases, namely Scopus, PubMed, Sage Journal, and Wiley Online Library, yielded 215 article findings. After the screening and review process, 7 eligible articles were selected based on the inclusion and exclusion criteria. Results: From the 7 selected research articles, it was found that media literacy has a positive relationship or influence on adolescent smoking behavior. This is evident from various research findings that show media literacy can increase knowledge and awareness of depictions of encouragement to smoke in the media they see and/or hear. These results were found from research on 4 continents, and no research results from the African and South American continents met the inclusion criteria. Conclusion: It is shown that media literacy is considered effective in increasing adolescents' knowledge and awareness of how the media tries to persuade them to try smoking, continue smoking, or vape. The results suggest developing learning modules or curricula that introduce and discuss media literacy in schools, either intracurricular, co-curricular, or extracurricular. Suggestions for future research include developing media literacy research tailored to local wisdom conditions and its application to measure or intervene in other risky health behaviors.